Outcome Expectations and Physical Activity in Persons with Longstanding Multiple Sclerosis - Morrison, Janet D. (2014)
Research suggests that persons with multiple sclerosis (MS) are much less physically active than the general population and that increased physical activity in persons with MS is associated with numerous benefits such as improvements in fatigue, mobility and quality of life (Motl & Pilutti, 2012). Potentially modifiable theory-based determinants of physical activity behavior need to be identified so that researchers may study their effectiveness in randomized clinical trials and clinicians may integrate them into practice to promote physical activity in this population. The purpose of this study was to explore the multidimensional (physical, social, and self-evaluative) outcome expectations for physical activity among persons with longstanding MS. A sample of 369 participants diagnosed with MS for more than 15 years completed surveys to measure multidimensional outcome expectations for exercise, MS functional limitations, and physical activity using two different instruments – one measuring physical activity engagement and the other physical activity capability. Results indicated that MS functional limitation was the strongest predictor of both physical activity engagement and physical activity capability. Physical and social outcome expectations contributed to the model explaining 12% of the variation in physical activity engagement while none of the outcome expectancy dimensions (physical, social, or self-evaluative) contributed to the model explaining variation in physical activity capability. While analyses of cross-sectional data does not infer causation, these findings suggest that positive physical and social outcome expectations for physical activity are associated with engagement in physical activity as well as being potential sources of motivation for increasing physical activity behavior in individuals living with longstanding MS.